Nosemosis in Africanized Honey Bee Colonies (Apis mellifera) in the Tropical Conditions of Costa Rica: Nosema apis or Nosema ceranae - Calderón, Rafael A. (2021)
The presence of nosemosis in Africanized honey bees in Costa Rica was studied. A total of 75 samples of adult bees from different country regions were selected for molecular diagnosis of nosemosis. Prior to PCR tests, Nosema spp. spores were morphologically identified in most of the bee samples using a light microscopy at 40x magnification. According to molecular analyses, most of the bee samples were found to be infected with Nosema ceranae. However, colonies showed no clinical signs of infection at any time during the sampling period, none of them being infected with Nosema apis. Surprisingly, 29.3% of the bee samples tested PCR negative to nosemosis. The origin of the bee samples collected from apiaries located in four of the seven provinces of Costa Rica showed the microsporidium is widely spread throughout the main beekeeping areas of the country. The pathological consequences of N. ceranae in Africanized honey bee colonies have not been well determined. Because of reports of honey bee colony losses in Europe related to microsporidian infections, the virulence of N. ceranae in Africanized honey bees needs to be studied.